(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Monkeys are phylogenetically close to humans and are therefore used in a lot of research models. This study aimed to determine the basic physiological and haematological parameters in four different species of captive monkeys during the rainy season. Fourteen adult monkeys at the University of Ibadan Zoological Garden were used for this study (3 - Cercocebus sebaeus, 3 - Cercopithecus mona, 3- Erythrocebus patas and 5- Papio Anubis). Dry-bulb temperature and relative humidity were recorded concurrently with the measurement of rectal temperature (RT), body surface temperatures (BST), respiratory (RR) and heart rates (HR). Blood sample were collected for the evaluation of haematological parameters. The dry-bulb temperature and relative humidity were 25.9℃ and 75%, respectively. The Erythrocebus patas monkey had mean RT value of 38.23 ± 0.2℃, while the Cercocebus sebaeus monkey had 38.87 ± 0.7℃ when compared to that of Papio anubis and Cercopithecus mona monkey (38.4 ± 0.3℃ and 38.53 ± 0.6℃, respectively). The mean RR value of 40.0 ± 2.3 cycle/min in Erythrocebus patas monkey was significantly (p ˂ 0.05) higher than 27.33 ± 1.3 cycles/min and 21.60 ± 1.9 cycles/min in Papio anubis and Cercocebus sebaeus monkey, respectively. The mean bias difference of rectal temperature versus eye temperature (0.8643 ± 0.749) was significantly (p ˂ 0.05) lower than the mean bias differences of the rectal temperature versus forehead (2.19 ± 0.75), but was not statistically (p ˃ 0.05) different from the value of 1.471 ± 0.9 obtained in the comparison of rectal temperature versus base of the tail temperature. The haematological parameters were not significantly different among the species. In conclusion, the basic thermoregulatory apparatus and haematological parameters of the different species of monkeys were not significantly different and the values recorded were within the established range for the monkey.